Sarasinula marginata (Semper, 1885) (Mollusca, Soleolifera) from Belo Horizonte (MG, Brazil) as a potential intermediate host of Angiostrongylus costaricensis Morera & Céspedes, 1971 - Lima, Lais Clark; Massara, Cristiano Lara; Souza, Cecília Pereira de; Jannotti-Passos, Liana K.; Lenzi, Henrique Leonel (Revista do Instituto de Medicina Tropical de São Paulo, 1992)
Specimens of Sarasinula marginata were collected in kitchen and house gardens of Belo Horizonte, Minas Gerais. The suscetibility of these molluscs for Angiostrongylus costaricensis was tested by infecting 15 laboratory - reared slugs (F1). The positivity demonstrated was of 80.0%.